High-order connected moments expansion for the Rabi Hamiltonian - Amore, Paolo (2011)
We analyze the convergence properties of the connected moments expansion (CMX) for the Rabi Hamiltonian. To this end we calculate the moments and connected moments of the Hamiltonian operator to a sufficiently large order. Our large–order results suggest that the CMX is not reliable for most practical purposes because the expansion exhibits considerable oscillations.